Larval morphology, life cycle and nutritional values of Lepidostoma abruptum Banks 1931 (Trichoptera: Lepidostomatidae) from Lower-Hill Evergreen Forests of Southern Thailand - Suwannarat, Nannaphat; Laudee, Pongsak (Zootaxa, 2022)
The larval morphology, life cycle, and nutritional values of Lepidostoma abruptum Banks 1931 are described and discussed. The larval case is rectangular in cross section, made of rectangular pieces of leaf. The larva of L. abruptum shares the morphological characteristics of other Lepidostoma spp. which have been described from different countries and continents. The head capsule widths of 74 specimens were measured and plotted to determine the instars of the larvae. This species is non-seasonal. In addition, the moisture (68.87%) and dry-weight nutritional values of the specimens were determined: protein (49.08%), total fat (27.13%), total dietary fiber (5.9%), omega-3 (0.15%), omega-6 (6.04%), and omega-9 (11.7%). Larvae of this species live in small debris pools dominated with leaf litter and small branches.